Preliminary sensory evaluation of edible flowers from wild Allium species - D'Antuono, L Filippo; Manco, Manuela Agata (Journal of the science of food and agriculture, 2013)
BACKGROUND The use of edible flowers as an aesthetic and flavour component of specific dishes is gaining popularity, and their production is becoming an interesting niche market activity for growers. Allium is an important genus of flowering plants, also including traditional wild food species. The combination of tradition with the new uses of flowers is appealing, requiring, however, explorative acceptance assays for its exploitation. RESULTS The flowers of the native Mediterranean species Allium neapolitanum, A. roseum and A. triquetrum were subject to hedonic visual, smell and flavour evaluation. Panellists also indicated specific flavour notes and their opinion about the more suitable uses. All the species were positively rated. A. roseum was preferred for all respects; A. triquetrum obtained the lowest visual rating, whereas A. neapolitanum had the lowest flavour rating. A spicy note was the main determinant of high flavour ratings. Dishes retaining the visual appearance of flowers were indicated as more suitable to combine with Allium flowers. CONCLUSION This is the first attempt at sensory evaluation of Allium flowers. Nutritional and health promotion properties and toxicity risks do not represent major issues for these products, because of potentially low consumption levels. The main constraint for a wider use of Allium flowers is represented by the absence of a consolidated consumption habit and regular supply. © 2013 Society of Chemical Industry